A descriptive survey on the proxemics of selected middle class residences with sari-sari stores located in Quezon City - Torres, Eleanor Anne P.; Florendo, Raquel Baltazar (Quezon City P College of Home Economics, 2012)
The study focused on the microcultural proxemics of residences with sari-sari stores. The study sought to identify the following key points: 1) The considerations used in the space planning and space allocation of a sari-sari store within a residence, 2) The presence of fixed, semi-fixed and informal space features, 3) The characteristics of spaces in an integrated domestic and livelihood setting and 4) The influences of a home-based sari-sari store to the family's daily activities. The researcher employed a descriptive survey design incorporating both quantitative and qualitative methods. Purposive sampling was used to generate the six (6) respondents of the study. Using selection criteria, the respondents were chosen based on their 1) middle class classification 2) ownership of a home-based sari-sari store and 3) a sari-sari store with a floor area of at least four (4) square meaters. The selected area of study was Brgy. Krus na Ligas, Quezon City. The researcher administered close and open-ended interviews, ocular observations and notations, photo documentation and furniture, furnishings and equipment layout documentations to derive conclusions on the proxemics of merged retail and residential set-ups. Results of the study showed that space planning and allocation of home-based sari-sari stores were determined by available space, proximity to roads and family interests. Spaces within this set-up were characterized by semi-fixed and fixed feature spaces which determine the use of space. Sociopetal and sociofugal spaces were also observed in home-based sari-sari stores which increased or decreased interactions among family members. Findings also revealed that the sari-sari store did not incorporate a strict business arrangement which caused conflicts between household and store activities. In conclusion, the sari-sari store, although different in its function, became an extension of the household.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Domestic space -- Philippines -- Quezon City -- Kruz na Ligas; Home based businesses -- Philippines -- Quezon City -- Kruz na Ligas